INVESTIGATION OF THE RELATIONSHIP BETWEEN JOB SATISFACTION AND CAREER SATISFACTION AND WORK-LIFE BALANCE IN SPORTS MANAGERS - Bayansalduz, Mehmet; Yanar, Şenol; Can, Yusuf (Acta Scientiae et Intellectus, 2024)
The aim of this study is to examine the relationship between job satisfaction and career satisfaction and work-life balance in sports managers. In the study, it has also been analyzed if there is any significant difference in the sports managers’ job satisfaction, career satisfaction and work-life balance levels in terms of gender, age, duty status, year of service and level of education. 322 sports managers, who work at Department of Sports Service’s Central and Field Organization at least as a chief in the manager position, have been chosen with random sampling method and they have voluntarily participated in the study. In the study, Minnesota Satisfaction Questionnaire, developed by Weis et. all. (1967) and adapted Turkish version by Baycan (1985), and career satisfaction scale, developed by Vatansever (2008), and work-life balance scales, developed by Apaydin (2011), have been used as data collection tools. The survey form used as a data collection tool in the study included a personal information form consisting of 5 questions, questioning the gender, age, duty status, years of service and level of education. In the study, Pearson Correlation Analysis has been used for defining sports managers’ job satisfaction and career satisfaction’s correlation with work-life balance; T-test for binary grouping and Anova Analysis have been used for more than binary groups in order to determine if there is any significant difference in sports managers’ job satisfaction, career satisfaction and work-life balance levels in terms of the participants’ duty status, year of service and level of education.